Sputtering targets for thermally assisted magnetic recording media

The use of an FePt alloy and a nonmagnetic oxide with specific melting points in a sputtering target addresses thermal fluctuations and noise issues, enhancing magnetic recording media's thermal stability and signal-to-noise ratio for higher recording density.

JP7610224B2Active Publication Date: 2025-01-08TANAKA KIKINZOKU KOGYO KK +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021553622
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-01
Filing Date
2020-10-27
Publication Date
2025-01-08
Estimated Expiration
2040-10-27

AI Technical Summary

Technical Problem

Current magnetic recording media face challenges in increasing recording density due to thermal fluctuations and noise, which are exacerbated by finer magnetic crystal grains, and existing methods to refine grains and reduce intergranular interaction are inadequate.

Method used

A sputtering target containing an FePt alloy and a nonmagnetic oxide with a melting point between 800°C and 1100°C is used to form a granular structure, enhancing saturation magnetization and magnetocrystalline anisotropy, thereby improving thermal stability and signal-to-noise ratio.

Benefits of technology

The solution results in a magnetic recording medium with improved uniaxial magnetic anisotropy, thermal stability, and increased signal-to-noise ratio, enabling higher recording density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610224000007
    Figure 0007610224000007
  • Figure 0007610224000008
    Figure 0007610224000008
  • Figure 0007610224000009
    Figure 0007610224000009
Patent Text Reader

Abstract

[Problem] To provide a sputtering target that improves uniaxial magnetic anisotropy and is used to form a magnetic thin film with a granular structure in which FePt magnetic particles that form a thermal assist magnetic recording medium with improved thermal stability and SNR (signal-to-noise ratio) are isolated by an oxide. [Solution] A sputtering target for a thermal assist magnetic recording medium with an FePt alloy and a nonmagnetic material as principal constituents, characterized in that the nonmagnetic material is an oxide with a melting point in the range of 800–1100°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sputtering target for a thermally assisted magnetic recording medium, and more particularly to a sputtering target for a thermally assisted magnetic recording medium that is mainly composed of an Fe-Pt alloy and a nonmagnetic material. [Background technology]

[0002] In the magnetic disk of a hard disk drive, information signals are recorded in minute bits of the magnetic recording medium. In order to further improve the recording density of the magnetic recording medium, it is necessary to reduce the size of the bit that holds one piece of recorded information while also increasing the signal-to-noise ratio, which is an index of information quality. In order to increase the signal-to-noise ratio, it is essential to increase the signal or reduce the noise.

[0003] Currently, magnetic thin films with a granular structure of CoPt alloy-oxide are used as magnetic recording media for recording information signals (see, for example, Non-Patent Document 1). This granular structure consists of columnar CoPt alloy crystal grains and the crystal grain boundaries of the oxide surrounding them.

[0004] To increase the recording density of such magnetic recording media, it is necessary to reduce noise by smoothing the transition regions between recording bits. To smooth the transition regions between recording bits, it is essential to refine the CoPt alloy crystal grains contained in the magnetic thin film.

[0005] On the other hand, as the magnetic crystal grains become finer, the strength of the recording signal that each magnetic crystal grain can hold decreases. To achieve both finer magnetic crystal grains and stronger recording signals, it is necessary to reduce the center-to-center distance between the crystal grains.

[0006] On the other hand, as the CoPt alloy crystal grains in magnetic recording media become finer, the thermal stability of the recorded signal is lost due to the superparamagnetic phenomenon, resulting in the loss of the recorded signal, a phenomenon known as thermal fluctuation. This thermal fluctuation phenomenon is a major obstacle to achieving higher recording densities on magnetic disks.

[0007] To solve this problem, it is necessary to increase the magnetic energy of each CoPt alloy crystal grain so that the magnetic energy overcomes the thermal energy. The magnetic energy of each CoPt alloy crystal grain is determined by the product v×Ku of the volume v of the CoPt alloy crystal grain and the magnetocrystalline anisotropy constant Ku. Therefore, in order to increase the magnetic energy of the CoPt alloy crystal grain, it is essential to increase the magnetocrystalline anisotropy constant Ku of the CoPt alloy crystal grain (for example, see Non-Patent Document 2).

[0008] In addition, in order to grow CoPt alloy crystal grains with a large Ku into a columnar shape, it is essential to achieve phase separation between the CoPt alloy crystal grains and the grain boundary material. If the phase separation between the CoPt alloy crystal grains and the grain boundary material is insufficient and the intergranular interaction between the CoPt alloy crystal grains becomes large, the coercive force Hc of the magnetic thin film consisting of a granular structure of CoPt alloy-oxide becomes small, the thermal stability is impaired, and the thermal fluctuation phenomenon becomes more likely to occur. Therefore, it is also important to reduce the intergranular interaction between the CoPt alloy crystal grains.

[0009] It is possible to reduce the size of magnetic crystal grains and the center-to-center distance of magnetic crystal grains by refining the crystal grains in the Ru underlayer (an underlayer provided for controlling the orientation of a magnetic recording medium).

[0010] However, it is difficult to reduce the crystal grain size of the Ru underlayer while maintaining the crystal orientation (for example, see Non-Patent Document 3). As a result, the size of the crystal grains in the Ru underlayer of current magnetic recording media remains almost the same as when longitudinal magnetic recording media were replaced by perpendicular magnetic recording media, at about 7 nm to 8 nm.

[0011] On the other hand, from the viewpoint of improving the magnetic recording layer rather than the Ru underlayer, there have been studies on miniaturizing the magnetic crystal grains, specifically, increasing the amount of oxide added to the CoPt alloy-oxide magnetic thin film to reduce the volume ratio of the magnetic crystal grains and miniaturizing the magnetic crystal grains (for example, see Non-Patent Document 4). This method achieved miniaturization of the magnetic crystal grains. However, this method cannot reduce the center-to-center distance of the magnetic crystal grains because the width of the crystal grain boundary increases due to the increase in the amount of oxide added.

[0012] Also, the addition of a second oxide to the single oxide used in conventional CoPt alloy-oxide magnetic thin films has been investigated (see, for example, Non-Patent Document 5). However, when adding multiple oxide materials, there is no clear guideline for selecting the materials, and even now, investigations are continuing into oxides to be used as grain boundary materials for CoPt alloy crystal grains. The inventors have concluded that in order to realize the miniaturization of the magnetic crystal grains in the magnetic thin film and the reduction of the center-to-center distance of the magnetic crystal grains, it is necessary to contain oxides with low and high melting points (specifically, B oxide with a low melting point of 450°C). 2 O 3 and a high melting point oxide having a melting point higher than that of the CoPt alloy (about 1450°C) were found to be effective, 2 O 3 proposed a sputtering target for magnetic recording that contains a CoPt alloy and an oxide, the CoPt alloy containing a high melting point oxide (Patent Document 1).

[0013] On the other hand, instead of CoPt alloy, L1 0 FePt alloys having this structure have attracted attention as materials for ultra-high density recording media, and a granular-structure magnetic thin film in which FePt magnetic particles are isolated by C (carbon) has been proposed as a magnetic recording medium for next-generation hard disks employing a thermally assisted magnetic recording method (Patent Document 2). However, since C (carbon) is a difficult-to-sinter material, it is extremely difficult to obtain a dense sintered body, and there is a problem that a large amount of particles are generated during sputtering. In addition, as will be described later, experiments by the present inventors have shown that when C (carbon) is used as a grain boundary material for FePt magnetic particles, the saturation magnetization (Ms grain It was found that the saturation magnetization becomes lower. A lower saturation magnetization is undesirable because it reduces the thermal stability. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] WO2018 / 083951 publication [Patent Document 2] Patent No. 5946922 [Non-patent literature]

[0015] [Non-Patent Document 1] T. Oikawa et al., IEEE TRANSACTIONS ON MAGNETICS, September 2002, VOL.38, NO.5, p.1976-1978 [Non-Patent Document 2] SN Piramanayagam, JOURNAL OF APPLIED PHYSICS, 2007, 102, 011301 [Non-Patent Document 3] SN Piramanayagam et al., APPLIED PHYSICS LETTERS, 2006,89, 162504 [Non-Patent Document 4] Y. Inaba et al., IEEE TRANSACTIONS ON MAGNETICS, July 2004, VOL.40, NO.4, p.2486-2488 [Non-Patent Document 5] I. Tamai et al., IEEE TRANSACTIONS ON MAGNETICS, November 2008, VOL.44, NO.11, p.3492-3495 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0016] The present invention aims to provide a sputtering target for use in depositing a granular-structure magnetic thin film in which FePt magnetic particles that constitute a thermally-assisted magnetic recording medium with improved uniaxial magnetic anisotropy, thermal stability, and SNR (signal-to-noise ratio) for even higher capacity are isolated by an oxide. [Means for solving the problem]

[0017] The inventors used various oxides as grain boundary materials to isolate the FePt magnetic particles, and measured the saturation magnetization (M s grain ) and the magnetocrystalline anisotropy constant (Ku grain By using oxides with a specific melting point range as the grain boundary material, the saturation magnetization (M s grain ) and magnetocrystalline anisotropy constant (Ku grain The present inventors discovered that a thermally assisted magnetic recording medium having high melting points can be obtained, and that it is effective to use a sputtering target containing an oxide having a melting point in a specific range as a non-magnetic material in order to form the thermally assisted magnetic recording medium, and thus completed the present invention.

[0018] According to the present invention, there is provided a sputtering target for thermally assisted magnetic recording media (hereinafter sometimes simply referred to as a "sputtering target" or "target") comprising an FePt alloy, a non-magnetic material, and unavoidable impurities, wherein the non-magnetic material is an oxide having a melting point of 800°C or more and 1100°C or less.

[0019] The sputtering target of the present invention is mainly composed of an FePt alloy, which is a constituent of magnetic crystal grains (micromagnets) in the granular structure of the magnetic thin film of a thermally assisted magnetic recording medium formed by sputtering.

[0020] Fe is a ferromagnetic metal element, and plays a central role in forming the magnetic crystal grains (micro magnets) of the granular structure of the magnetic thin film of the thermally assisted magnetic recording medium. From the viewpoint of increasing the magnetocrystalline anisotropy constant Ku of the FePt alloy crystal grains (magnetic crystal grains) in the magnetic thin film obtained by sputtering, and from the viewpoint of maintaining the magnetism of the FePt alloy crystal grains (magnetic crystal grains) in the magnetic thin film obtained, the content of Fe in the sputtering target of the present invention is preferably 40 mol% or more and 60 mol% or less, more preferably 45 mol% or more and 55 mol% or less, based on the total metal components.

[0021] Pt has a function of reducing the magnetic moment of the alloy by alloying with Fe in a predetermined composition range, and plays a role in adjusting the magnetic strength of the magnetic crystal grains. From the viewpoint of increasing the magnetocrystalline anisotropy constant Ku of the FePt alloy crystal grains (magnetic crystal grains) in the magnetic thin film of the thermally assisted magnetic recording medium obtained by sputtering, and from the viewpoint of adjusting the magnetism of the FePt alloy crystal grains (magnetic crystal grains) in the obtained magnetic thin film, the content of Pt in the sputtering target of the present invention is preferably 40 mol% to 60 mol%, more preferably 45 mol% to 55 mol%, based on the total metal components.

[0022] In addition to Fe and Pt, the sputtering target of the present invention may further contain one or more additional elements selected from Ag, Au, and Cu as metal components. These metal elements are mainly present in the L1 0 The amount of the additional metal element is not particularly limited as long as it is within a range that does not impair the properties of the magnetic thin film of the thermally assisted magnetic recording medium. For example, the content of the additional metal element in the sputtering target of the present invention is preferably 0 mol% or more and 20 mol% or less, more preferably 0 mol% or more and 10 mol% or less, based on the total metal components.

[0023] Hereinafter, in this specification, an alloy consisting of Fe and Pt will be referred to as an "FePt alloy", and an alloy containing one or more elements selected from Ag, Au, and Cu in addition to Fe and Pt will be referred to as an "FePt-based alloy".

[0024] The non-magnetic material contained in the sputtering target of the present invention is an oxide having a melting point of 800° C. to 1100° C. In a magnetic film formed by sputtering a target containing an oxide having a melting point of 800° C. to 1100° C., the oxide can be arranged as a grain boundary material of FePt magnetic particles, and a thermally assisted magnetic recording medium having the magnetic film has a surface roughness of about 950 emu / cm. 3 Saturation magnetization (M s grain ) and 2.5×10 7 erg / cm 3 The magnetocrystalline anisotropy constant (Ku grain ) can be realized. As will be described later in detail, as shown in Figs. 2 and 3, the lower the melting point of the oxide used as the grain boundary material of the FePt magnetic particles, the higher the saturation magnetization (M s grain ) is high, but when oxides with melting points below 800°C are used as grain boundary materials, the magnetocrystalline anisotropy constant (Ku grain ) is lower, and the saturation magnetization (M s grain ) and magnetocrystalline anisotropy constant (Ku grain ) cannot be increased at the same time. Therefore, the sputtering target of the present invention contains an oxide having a melting point of 800°C or more and 1100°C or less. By using this sputtering target, the oxide can function as a grain boundary material in a thermally assisted magnetic recording medium. Examples of oxides having a melting point of 800°C or more and 1100°C or less include SnO (melting point 1080°C), PbO (melting point 886°C), Bi 2 O 3 (melting point 817° C.) are particularly preferred.

[0025] The content of the nonmagnetic material in the sputtering target of the present invention is preferably 25 vol% to 40 vol%, more preferably 27 vol% to 36 vol%, and even more preferably 29 vol% to 32 vol%. By keeping the content of the nonmagnetic material within the above range, it is possible to reliably separate the FePt magnetic particles in the magnetic layer of a magnetic recording medium formed using the sputtering target of the present invention, making it easier to isolate the magnetic particles, and thus increasing the recording density.

[0026] Although the microstructure of the sputtering target of the present invention is not particularly limited, it is preferable that the metal phase and the oxide phase are finely dispersed in the microstructure, which makes it difficult for defects such as nodules and particles to occur during sputtering.

[0027] The sputtering target of the present invention can be produced, for example, as follows.

[0028] The FePt alloy molten metal is prepared by weighing each metal component to obtain a desired composition. Then, gas atomization is performed to prepare an FePt alloy atomized powder. The prepared FePt alloy atomized powder is classified so that the particle size is a desired particle size or less (for example, 106 μm or less).

[0029] The prepared FePt alloy atomized powder was mixed with oxide powder (SnO, PbO, and / or Bi) with a melting point of 800°C or more and 1100°C or less. 2 O 3 ), and if necessary, additional metal element powders (e.g., Ag, Au, and / or Cu) are added and mixed and dispersed in a ball mill to prepare a mixed powder for pressure sintering. By mixing and dispersing the FePt alloy atomized powder, the oxide powder, and if necessary, other metal element powders in a ball mill, it is possible to prepare a mixed powder for pressure sintering in which the FePt alloy atomized powder, the oxide powder, and if necessary, other metal element powders are finely dispersed.

[0030] Alternatively, as the FePt-based alloy atomized powder containing additional metal elements together with Fe and Pt, an oxide powder having a melting point of 800°C or more and 1100°C or less (SnO, PbO, and / or Bi 2 O 3 ) may be added and mixed and dispersed in a ball mill to prepare a mixed powder for pressure sintering.

[0031] The prepared mixed powder for pressure sintering is molded by pressure sintering, for example, by vacuum hot pressing to prepare a sputtering target. The mixed powder for pressure sintering is mixed and dispersed by a ball mill, and the FePt alloy atomized powder, the oxide powder, and other metal element powders as necessary are finely dispersed, or the FePt alloy atomized powder and the oxide powder are finely dispersed, so that when sputtering is performed using the sputtering target obtained by this manufacturing method, problems such as the generation of nodules and particles are unlikely to occur. The method for pressure sintering the mixed powder for pressure sintering is not particularly limited, and may be a method other than the vacuum hot pressing method, for example, the HIP method or the like may be used.

[0032] When preparing the mixed powder for pressure sintering, it is not limited to the alloy atomized powder, and powder of each metal may be used. In this case, Fe metal powder, Pt metal powder, the oxide powder, and other metal element powders as necessary are mixed and dispersed in a ball mill to prepare the mixed powder for pressure sintering. Effect of the Invention

[0033] The sputtering target for thermally assisted magnetic recording media of the present invention can form a granular-structure magnetic thin film for a high-density magnetic recording medium with improved uniaxial magnetic anisotropy, thermal stability, and SNR. [Brief description of the drawings]

[0034] [Figure 1] Magnetization curve of an FePt granular magnetic recording medium having an FePt-30 vol% X (X is a non-magnetic material) magnetic film. [Diagram 2]1 is a graph showing the relationship between the melting point and magnetocrystalline anisotropy (Kugrain) of the nonmagnetic material of an FePt granular magnetic recording medium having an FePt-30 vol % X (X is a nonmagnetic material) magnetic film. [Diagram 3] 1 is a graph showing the relationship between the melting point and saturation magnetization (Ms grain) of the non-magnetic material of an FePt granular magnetic recording medium having an FePt-30 vol % X (X is a non-magnetic material) magnetic film. [Figure 4] 1 is a graph showing the relationship between the melting point and coercivity (Hc) of the non-magnetic material of an FePt granular magnetic recording medium having an FePt-30 vol % X (X is a non-magnetic material) magnetic film. [Diagram 5] X-ray diffraction profile obtained by measuring the crystal orientation of the perpendicular and in-plane components of a thermally assisted FePt granular magnetic recording medium using X-ray diffraction. [Figure 6] 1 is a graph showing the relationship between the melting point and the degree of order (Sin) of the non-magnetic material of an FePt granular magnetic recording medium having an FePt-30 vol % X (X is a non-magnetic material) magnetic film. [Figure 7] 1 is a graph showing the relationship between the melting point and crystal grain size (GD) of the non-magnetic material of an FePt granular magnetic recording medium having an FePt-30 vol% X (X is the non-magnetic material) magnetic film. [Figure 8] 1 is a graph showing the relationship between crystal grain size (GD) and degree of order (Sin) of an FePt granular magnetic recording medium having an FePt-30 vol% X (X is a nonmagnetic material) magnetic film. [Figure 9] 1 is a graph showing the relationship between crystal grain size (GD) and coercive force (Hc) of an FePt granular magnetic recording medium having an FePt-30 vol% X (X is a nonmagnetic material) magnetic film. [Figure 10] 1 is a graph showing the relationship between the degree of order (Sin) and the coercive force (Hc) of an FePt granular magnetic recording medium having an FePt-30 vol % X (X is a nonmagnetic material) magnetic film. [Figure 11] 1 is a graph showing the relationship between the content of nonmagnetic material and magnetocrystalline anisotropy (Kugrain) in an FePt granular magnetic recording medium having an FePt-SnO magnetic film. [Figure 12]1 is a graph showing the relationship between the content of nonmagnetic material and saturation magnetization (Ms grain) of an FePt granular magnetic recording medium having an FePt-SnO magnetic film. [Figure 13] 1 is a graph showing the relationship between the content of nonmagnetic material and the coercive force (Hc) of an FePt granular magnetic recording medium having an FePt-SnO magnetic film. EXAMPLES

[0035] The present invention will be described in detail below, but the present invention is not limited thereto.

[0036] [Example 1] A target of FePt-30vol%X (X is a nonmagnetic material) was prepared by mixing each nonmagnetic material shown in Table 1 at 30vol%.

[0037] First, 50Fe-50Pt alloy atomized powder was prepared. Specifically, each metal was weighed so that the composition was Fe: 50at% and Pt: 50at%. Both metals were heated to 1500℃ or higher to form a molten alloy, and gas atomized to produce 50Fe-50Pt alloy atomized powder.

[0038] The prepared 50Fe-50Pt alloy atomized powder was classified using a 150 mesh sieve to obtain 50Fe-50Pt alloy atomized powders each having a particle size of 106 μm or less.

[0039] To obtain a composition of (50Fe-50Pt)-30vol%X (X is each nonmagnetic material shown in Table 1), powder of a nonmagnetic material shown in Table 1 as X was added to the classified 50Fe-50Pt alloy atomized powder, and mixed and dispersed in a ball mill to obtain 16 types of mixed powders for pressure sintering, each containing a different nonmagnetic material.

[0040] Next, the prepared mixed powder for pressure sintering was used to obtain a sintered body by hot pressing under vacuum conditions. For example, SnO was used as the non-magnetic material X, and the sintering temperature was 960°C, the sintering pressure was 24.5 MPa, the sintering time was 60 minutes, and the atmosphere was 5×10 -2Hot pressing was performed under vacuum conditions of 0.1 Pa or less to produce a stepped target (50Fe-50Pt)-30vol%SnO with dimensions of (upper) 153.0mm diameter x 1.0mm + (lower) 161.0mm diameter x 4.0mm. The relative density of the target produced was 96.5%. For the other non-magnetic materials, sintered bodies were prepared under the conditions shown in Table 2 to produce targets.

[0041] The prepared target was used for sputtering in a DC sputtering device (Canon Anelva) to form a magnetic thin film consisting of (50Fe-50Pt)-30vol%X on a glass substrate, and samples for magnetic property measurement and microstructural observation were prepared. Specifically, a CoW seed layer was formed on a glass plate to a thickness of 80 nm by DC sputtering (1.5 kW, 0.6 Pa), an MgO underlayer was formed on the CoW seed layer to a thickness of 5 nm by RF magnetron sputtering (0.5 kW, 4.0 Pa), an FePt-30 vol%X (X is a non-magnetic material shown in Table 1) magnetic film was formed on the MgO underlayer to a thickness of 10 nm by DC sputtering (0.1 kW, 8.0 Pa, Ar gas), and a C surface protective layer was formed on the magnetic film to a thickness of 7 nm by DC sputtering (0.3 kW, 0.6 Pa) to obtain a thermally assisted FePt granular magnetic recording medium, and the magnetic properties (magnetic crystal anisotropy and saturation magnetization) were measured using a SQUID-VSM (Max 7T) and a PPMS torque magnetometer (Max 9T). The measurement results are shown in Table 1, and the magnetization curve is shown in Figure 1. In addition, the melting point of the non-magnetic material and the magnetocrystalline anisotropy (K u grain ), saturation magnetization (M s grain ), Coercivity(H c ) are plotted in Figures 2, 3, and 4. Furthermore, the crystal orientation of the perpendicular and in-plane components of the thermally-assisted FePt granular magnetic recording medium was measured by X-ray diffraction, and the results are shown in Figure 5.

[0042] In addition, in the results of measuring the crystal orientation of the perpendicular component in FIG. 5, the degree of order (S in ) and measure the melting point and degree of order (S in The relationship between the degree of order S and the in represents the degree to which Fe and Pt atoms are repeatedly stacked in the film thickness direction. When Fe and Pt atoms are completely repeatedly stacked without defects, S in is 1.0 (theoretical value). In addition, if Fe and Pt atoms are not completely stacked, S in becomes 0.

[0043]

number

[0044] Furthermore, using the FePt(200) diffraction peak in the in-plane diffraction profile in Figure 5, the grain diameter (GD) of the thermally-assisted FePt granular magnetic recording medium was evaluated according to equation (2), and the relationship between the melting point of the nonmagnetic material and the grain diameter (GD) is plotted in a graph shown in Figure 7.

[0045]

number

[0046] Furthermore, the correlation between the degree of order and the grain size is shown in Figure 8. c ) and grain size is shown in Fig. 9. c The correlation between the degree of ordering and the degree of crystal order is shown in FIG.

[0047] [Table 1]

[0048] [Table 2]

[0049] 1 shows that the hysteresis of the magnetic recording medium depends on the grain boundary material (the non-magnetic material of the sputtering target), and good results are obtained when SnO (melting point 1080°C), MnO (melting point 1945°C), MgO (melting point 2852°C) and C (melting point 3500°C) are used as the grain boundary material. Also, Table 1 shows that the coercivity is high when SnO (melting point 1080°C), MnO (melting point 1945°C) and C (melting point 3500°C) are used.

[0050] From Fig. 2, the magnetocrystalline anisotropy (K grain ) depends on the grain boundary material (non-magnetic material of the sputtering target). The grain boundary materials are SnO (melting point 1080℃), PbO (melting point 886℃), Bi 2 O 3 (Melting point 817℃), GeO 2 (melting point 1115°C) and BN (melting point 2973°C) are used. 7 erg / cm 3 It can be seen that the film exhibits a high magnetocrystalline anisotropy.

[0051] From FIG. 3, the saturation magnetization (M s grain ) depends on the grain boundary material (non-magnetic material of the sputtering target), and a high correlation is observed in particular with the melting point of the grain boundary material. The lower the melting point, the higher the saturation magnetization. 2 O 3 (melting point 817℃) is used, 950 emu / cm 3 More than 1000 emu / cm, especially when using SnO (melting point 1080°C). 3 It can be seen that the magnetization is equal to or greater than the saturation magnetization.

[0052] From Fig. 4, the coercive force (H c) does not show any correlation with the melting point of the grain boundary material (non-magnetic material of the sputtering target). However, when PbO (melting point 886°C) is used as the grain boundary material, 2 O 3 It can be seen that when SnO (melting point 817°C) is used, the coercive force is 26 kOe, and when SnO (melting point 1080°C) is used, the coercive force is about 30 kOe.

[0053] As shown in FIG. 5, in the perpendicular diffraction profile of the magnetic recording medium, when SnO (melting point 1080°C) is used as the grain boundary material, the FePt (001) diffraction peak is larger than that of other grain boundary materials C (melting point 3500°C) and B 2 O 3 (melting point 450℃), TiO 2 It can be seen that the FePt(110) diffraction peak is stronger than that of the other grain boundary materials C (melting point 3500°C) and B (melting point 1857°C). In addition, in the in-plane diffraction profile of the magnetic recording medium, noise is reduced overall, and when SnO (melting point 1080°C) is used as the grain boundary material, the FePt(110) diffraction peak is stronger than that of the other grain boundary materials C (melting point 3500°C) and B (melting point 1857°C). 2 O 3 (melting point 450℃), TiO 2 It can be seen more clearly that the melting point is stronger than that of SnO (melting point 1,857°C). Therefore, it can be confirmed that when SnO is used, the perpendicular direction becomes the easy axis direction.

[0054] From FIG. 6, the relationship between the degree of order of the magnetic recording medium and the melting point of the grain boundary material (the nonmagnetic material of the sputtering target) is correlation However, when SnO (melting point 1080°C) is used as the grain boundary material, the degree of order approaches 1.0, indicating a high degree of order.

[0055] From FIG. 7, the relationship between the crystal grain size of the magnetic recording medium and the melting point of the grain boundary material (the nonmagnetic material of the sputtering target) is correlation However, when SnO (melting point 1080°C) is used as the grain boundary material, a large crystal grain size of approximately 8 nm is shown.

[0056] As can be seen from FIG. 8, the order and crystal grain size of the magnetic recording medium are good. correlation It can be seen that the larger the crystal grain size, the higher the degree of order.

[0057] From Fig. 9, the coercive force (H c ) and the grain size is good. correlation It can be seen that the larger the crystal grain size, the higher the coercivity.

[0058] From Fig. 10, the coercive force (H c ) and the degree of regularity is good. correlation It can be seen that the higher the degree of order, the higher the coercive force.

[0059] From the above results, it is clear that the ferromagnetic alloy has good hysteresis, high coercive force, and high crystal magnetic anisotropy (K grain ), high saturation magnetization (M s grain It was found that the grain boundary material that can satisfy all of the requirements, that the easy axis direction is perpendicular to the plane, that the degree of order is high, and that the columnar growth of the crystal grains is good, is an oxide having a melting point of 800°C or more and 1100°C or less, such as SnO. In this embodiment, SnO, PbO, or Bi 2 O 3 Although only an example in which an oxide having a melting point in the same range is used as the grain boundary material is shown, it is believed that the same effect will be obtained when an oxide having a melting point in the same range is used as the grain boundary material.

[0060] [Example 2] Next, the same procedure as in Example 1 was repeated except that the 50Fe-50Pt alloy atomized powder was changed to 47.5Fe-47.5Pt-5Y alloy atomized powder (Y is Au, Ag, or Cu) containing 5 at% of Au, Ag, or Cu as shown in Table 3, under the conditions of sintering temperature: 960°C, sintering pressure: 24.5 MPa, sintering time: 60 min, and atmosphere: 5×10 -2 Hot pressing was performed under vacuum conditions of 0.01 Pa or less to produce a stepped FePtY-30vol%SnO (Y is Au, Ag or Cu) target and a thermally assisted FePt granular magnetic recording medium with dimensions of (upper) 153.0×1.0 mm diameter + (lower) 161.0×4.0 mm diameter, and the magnetic properties (magnetic crystal anisotropy and saturation magnetization) were measured. The measurement results are shown in Table 3.

[0061] [Table 3]

[0062] By adding Au, Ag or Cu, the saturation magnetization (M s grain ) decreases, and the magnetocrystalline anisotropy (K u grain ) increases, and the coercivity (H c ) tends to increase, but the range of variation is small, and it can be confirmed that the FePt-based alloy sputtering target containing Au, Ag, or Cu can be used as a thermally assisted magnetic recording medium to exhibit the same magnetic properties as the 50Fe-50Pt alloy sputtering target. On the other hand, as a sputtering target, the relative density of (50Fe50Pt)-30vol%SnO is 96.5%, the relative density of (47.5Fe47.5Pt5Au)-30vol%SnO is 98.2%, the relative density of (47.5Fe47.5Pt5Ag)-30vol%SnO is 97.8%, and the relative density of (47.5Fe47.5Pt5Cu)-30vol%SnO is 97.3%, and it can be confirmed that the FePt-based alloy sputtering target containing Au, Ag, or Cu can improve the relative density.

[0063] [Example 3] Next, the same procedure as in Example 1 was carried out except that the content of the non-magnetic material SnO was changed as shown in Table 4, sintering temperature: 960°C, sintering pressure: 24.5 MPa, sintering time: 60 minutes, atmosphere: 5×10 -2 Hot pressing was performed under vacuum conditions of 100 Pa or less to produce a stepped FePt-SnO target (upper row) with a diameter of 153.0 × 1.0 mm + (lower row) with a diameter of 161.0 × 4.0 mm and a thermally assisted FePt granular magnetic recording medium, and the magnetic properties (magnetic crystal anisotropy and saturation magnetization) were measured. The measurement results are shown in Table 4. The magnetic crystal anisotropy (K u grain ), saturation magnetization (M s grain ), Coercivity(H c ) are plotted in Figures 11, 12, and 13.

[0064] [Table 4]

[0065] 11 and 12, the saturation magnetization (M s grain ) and magnetocrystalline anisotropy (K u grain ) is maximum, and decreases as the content increases when the content is 25 vol% or more. When the content of the non-magnetic material SnO is 20 vol% or more and 45 vol% or less, it is 950 emu / cm 3 Above 980 emu / cm, especially when 20 vol% or more and 40 vol% or less 3 High saturation magnetization (M s grain ) can be expressed, and when the content of the non-magnetic material SnO is 20 vol% or more and 45 vol% or less, 2.5 × 10 7 erg / cm 3 Above 2.6×10 7 erg / cm 3 High magnetocrystalline anisotropy (K u grain ) can be expressed.

[0066] From FIG. 13, the coercive force (Hc) is maximum when the content of the non-magnetic material SnO is 30 vol% and 35 vol%, and the content of the non-magnetic material SnO is 25 vol% to 40 vol%. below It can be seen that a high coercive force exceeding 25 kOe can be achieved at this temperature.

[0067] From the above, when the content of the non-magnetic material SnO is 25 vol% or more and 40 vol% or less, the saturation magnetization (M s grain ), magnetocrystalline anisotropy (K u grain ) and coercive force (Hc) all increase.

[0068] The thermally assisted magnetic recording medium having the above magnetic properties and structure has a high saturation magnetization (M s grain It is believed that the high uniaxial magnetic anisotropy increases the signal of the thermally assisted magnetic recording medium and improves the SNR (signal-to-noise ratio). It is also believed that the high uniaxial magnetic anisotropy increases the magnetic energy of the thermally assisted magnetic recording medium and improves the thermal stability.

Claims

1. A sputtering target for a thermally assisted magnetic recording medium, comprising an FePt alloy, a non-magnetic material, and unavoidable impurities, wherein the non-magnetic material is an oxide having a melting point of 800°C or higher and 1100°C or lower.

2. A sputtering target for a thermally assisted magnetic recording medium, comprising an FePt-based alloy containing one or more elements selected from Ag, Au, and Cu, a non-magnetic material, and unavoidable impurities, wherein the non-magnetic material is an oxide having a melting point of 800°C or higher and 1100°C or lower.

3. The non-magnetic material is SnO, PbO, Bi 2 O 3 3. The sputtering target for a thermally assisted magnetic recording medium according to claim 1, wherein the sputtering target is one or more oxides selected from the following:

4. 4. The sputtering target for a thermally assisted magnetic recording medium according to claim 1, wherein the non-magnetic material is contained in an amount of 25 vol % or more and 40 vol % or less relative to the sputtering target for a thermally assisted magnetic recording medium.

Citation Information

Patent Citations

  • Herbicidal composition and manufacturing method thereof

    JP1984046922B2

  • Sputtering target for recording medium and magnetic recording medium

    JP2003313659A

  • Ferromagnetic-material sputtering target of nonmagnetic-material particle dispersion type

    WO2010110033A1

  • Magnetic recording medium and manufacturing method for magnetic recording medium

    WO2011132747A1

  • Fe-pt ferromagnetic sputtering target and method for producing same

    WO2012086578A1